Investigation of Various Metal Recoveries from Zinc Plant Leach Residue by Choline-Chloride Agent - Rusen, Aydin; Ali Topcu, Mehmet (Current Physical Chemistry, 2017)
Aims: Zinc plant leach residues as well as other industrial wastes have remarkable economic value due to the contents of the high amount of valuable metals and also having a risk of polluting to the environment. Observations: It is generally accepted that these leach residues must be evaluated to eliminate the negative effects on human life. In this study, therefore, zinc and lead recoveries were investigated from environmentally hazardous zinc plant leach residue by means of a novel leaching agent namely choline chloride/urea mixture differently from conventional solvents. For this reason, the choline chloride/urea mixture which is ecocredential in 2:1 molar ratio was used in different concentration in the 25-95°C temperature range. Result: According to the results, zinc and lead recovery increased with increasing the reaction temperature but also undesirable increases in iron dissolution. The maximum zinc recovery which could be achieved was 56% for leach residue by pure choline chloride/urea mixture.
Keywords: urea